Nested PCR for diagnosing scabies infestation. (1st October 2018) - Hahm, J.E.; Kim, C.W.; Kim, S.S.
Summary: Scabies is a highly contagious, very itchy infestation on the skin of mites called Sarcoptes scabiei . Although it is more prevalent in developing countries, outbreaks in elderly care facilities are a growing problem for developed countries. Mineral oil examination, which involves gently scraping the patient's skin with mineral oil, transferring scales to a glass slide, and then identifying the mites or eggs with a microscope, is regarded as the gold standard in diagnosing scabies, but it is not always accurate. This study, from South Korea, aimed to enhance the accuracy of laboratory diagnosis of scabies. The authors tested a different way of detecting scabies, called nested polymerase chain reaction (PCR) and compared nested PCR results with those of conventional diagnostic method, to see which is more accurate. Nested PCR is a way of making many copies of a specific DNA region in a test tube, making it possible to look for DNA from the mites that cause scabies. Clinically suspected scabies patients underwent mineral oil examination. The diagnosis was positive for scabies when mites or eggs were found under the microscope, and patients were then designated as 'microscopy‐positive'. Patients in the 'microscopy‐negative' group presented with negative microscopic results, meaning that mites or eggs had not been seen under a microscope. Skin scrapings were collected from both groups for PCR. Of the total 63 samples, 28 were microscopy‐positive and 35 were negative. All microscopically proven scabies cases were positive with nested PCR. Among microscopy‐negative ones, S. scabiei DNA was detected in 9 samples. This means that in 9 of the 35 cases where mites or eggs were not found under a microscope using the normal testing method, mites' DNA was indeed found using nested PCR. If sensitivity (accuracy) of nested PCR is considered 100%, then sensitivity of microscopy is 75.68%. Therefore, nested PCR can be successfully used as an alternative method for diagnosing suspected scabies cases. Furthermore, infection‐control measures and treatments can be initiated before it spreads too widely, minimizing the risk of outbreaks.